The Obama administration and educational reform - Zamani-Gallaher, Eboni M., 1971- (Advances in education in diverse communities ;, 2014)
Arguably, since the day he was elected, President Barack Obama met great anticipation from scores of Americans regarding the forward course our nation desired economically, socially, and educationally. The promise of progress and social mobility that millions of U.S. families hope to attain can be unlocked through the educational enterprise. Unfortunately, while the United States educates all children, all children do not receive the same education. Hence, prospects for a better future for many are thwarted from the onset given the inequities in P-12 education. Furthermore, the pendulum is swinging as higher learning is becoming increasingly obstructed for many Americans across income brackets, gender, racial/ethnic backgrounds, abilities, and geographic areas.